Highly Tough, Li‐Metal Compatible Organic–Inorganic Double‐Network Solvate Ionogel. Issue 22 (24th April 2019) - Yu, Le; Guo, Songtao; Lu, Yue; Li, Yaqian; Lan, Xiwei; Wu, Dabei; Li, Ruguang; Wu, Siqi; Hu, Xianluo
Abstract: Ionogels are considered promising electrolytes for safe lithium‐ion batteries (LIBs) because of their low flammability, good thermal stability, and wide electrochemical stability window. Conventional ionic liquid‐based ionogels, however, face two main challenges; poor mechanical property and low Li‐ion transfer number. In this work, a novel solvate ionogel electrolyte (SIGE) based on an organic–inorganic double network (DN) is designed and fabricated through nonhydrolytic sol–gel reaction and in situ polymerization processes. The unprecedented SIGE possesses high toughness (bearing the deformation under the pressure of 80 MPa without damage), high Li‐ion transfer number of 0.43, and excellent Li‐metal compatibility. As expected, the LiFePO4 /Li cell using the newly developed SIGE delivers a high capacity retention of 95.2% over 500 cycles, and the average Coulombic efficiency is as high as 99.8%. Moreover, the Ni‐rich LiNi0.8 Co0.1 Mn0.1 O2 (NCM811)/Li cell based on the modified SIGE achieves a high Coulombic efficiency of 99.4%, which outperforms previous solid/quasi‐solid‐state NCM811‐based LIBs. Interestingly, the SIGE‐based pouch cells are workable under extreme conditions (e.g., severely deforming or clipping into segments). In terms of those unusual features, the as‐obtained SIGE holds great promise for next‐generation flexible and safe energy‐storage devices. Abstract : A double‐network (DN) solvate ionogel electrolyte (SIGE) with excellent mechanical properties, high thermal stability, and outstanding electrochemical properties is achieved, benefitting from the strong coupling of the DN structures and the solvate ionic liquid. The present SIGE is a very promising candidate to develop high‐performance and high‐safety flexible energy‐storage devices.